Chimeric antigen receptor T cell therapy: 25 years in the making. Issue 3 (May 2016) - Gill, Saar; Maus, Marcela V.; Porter, David L.
Abstract: Chimeric antigen receptor (CAR) T cell therapy of cancer is generating enormous enthusiasm. Twenty-five years after the concept was first proposed, major advances in molecular biology, virology, and good manufacturing practices (GMP)-grade cell production have transformed antibody-T cell chimeras from a scientific curiosity to a fact of life for academic cellular immunotherapy researchers and, increasingly, for patients. In this review, we explain the preclinical concept, outline how it has been translated to the clinic, and draw lessons from the first years of CAR T cell therapy for the practicing clinician.